List-rationalizable choice - Kemal Yıldız (Theoretical Economics, 2016)
A choice function is list rational(izable), if there is a fixed list such that for each choice set, successive comparison of the alternatives by following the list retrieves the chosen alternative. We extend the formulation of list rationality to stochastic choice setup. We say two alternatives are related if the stochastic path independence condition is violated between these alternatives. We show that a random choice function is list rational if and only if this relation is acyclic. Our characterization for deterministic choice functions follows as a corollary. By using this characterization, we relate list rationality to two-stage choice procedures.
Keywords: D01; 330; Rationalization; list; choice functions; random choice; path independence; acyclicity